Assessment of Societal Health Risks: Spatial Distribution and Potential Hazards of Toxic Metals in Street Dust Across Diverse Communities - Isinkaralar, Oznur; Isinkaralar, Kaan; Ambade, Balram (Springer Science and Business Media LLC, 2024)
AbstractOn a global scale, the urban design of city centers is a topic of discussion concerning various aspects such development and its impact on public health. This research examines the health effects of urban agglomeration in city centers with compact, close development. In this work, the potentially toxic metals in street dust were studied by collecting and measuring street dust samples, measuring trace metal concentrations, and using index assessment, spatial analysis, correlation analysis, and health risk assessment models. Eskişehir, located in the part of Central Anatolia close to the Aegean region, west Türkiye, has been widely recognized as one of the most popular, known for having many narrow and old buildings in urban environments. The present paper investigates the atmospheric dust-related chemical speciation, urban environmental pollution, and human health risks in Eskişehir City by studying 66 dust samples collected at 11 points in the selected streets in August 2023. the study found that the concentrations of trace elements followed the order Cr > Ni > Pb > Cd > Cu. The primary source of these high levels is believed to be traffic-related contamination involving Cd, Pb, and Ni. The assessment of non-carcinogenic health risks has shown that the significant sources of potential toxic metals exposure for both children and adults are i) through ingestion and ii) dermal contact. The Hazard index (HI) for selected metals decreased in the order Cr > Pb > Ni > Cd > Cu for both children and adults without imposing possible non-carcinogenic risk (HI<1). On the contrary, Cr posed cancer risks above the safety threshold (> 10-4) through ingestion. Based on the available findings, Eskişehir still suffers from considerable environmental and ecological degradation and severe health risks due to street dust contamination. However, while high pollution was detected in the city center, where there is commercial land use, low values were observed in the region, rich with the water surface, bicycle paths, landscape design, and where traffic is slowed down.
Keywords: 13. Climate action; 11. Sustainability; 12. Responsible consumption; 3. Good health